2020
DOI: 10.1007/s13770-020-00253-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Filtered Bone Marrow Aspirate and Biomimetic Scaffold for the Treatment of Knee Osteochondral Lesions: Cellular and Early Clinical Results of a Single Centre Case Series

Abstract: BACKGROUND: Osteochondral injury is a very common orthopaedic pathology, mainly affecting young, active population, with limited current treatment options. Herein we are presenting cellular and early clinical data of a patient series treated for chronic osteochondral lesions in the knee with a filter-based intra-operative bone marrow aspirate (BMA) separation device. METHODS: Fifteen patients with chronic knee osteochondral lesions (60% females, 19-59 years) were included in this prospective case series. Filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In this regard, the efficacy of filtered bone marrow aspirate containing MSCs in combination with biomimetic collagen-hydroxyapatite scaffold in KOA was investigated on 15 patients. This research showed significant improvement in the status of the patients [92]. PRP is one of the cartilage growth factors which is rich in TGF-β, Koh et al reported that the injection of MSCs in combination with PRP into the joint cavity showed significant improvement in the treatment of OA [93].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 69%
“…In this regard, the efficacy of filtered bone marrow aspirate containing MSCs in combination with biomimetic collagen-hydroxyapatite scaffold in KOA was investigated on 15 patients. This research showed significant improvement in the status of the patients [92]. PRP is one of the cartilage growth factors which is rich in TGF-β, Koh et al reported that the injection of MSCs in combination with PRP into the joint cavity showed significant improvement in the treatment of OA [93].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 69%
“…7,8,10,11,21 There have been several clinical studies supporting the use of BMAC for the treatment of cartilage lesions. 9,10,[22][23][24][25] As the use of BMAC for osteochondral lesions continues to be evaluated, we offer a technique for use in treating OCD lesions, with tips from our experience in implementing this technique. Another technique has described in which the parent bone of an OCD undergoes microfracture to release mesenchymal cells on the parent bone.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 10 , 11 , 21 There have been several clinical studies supporting the use of BMAC for the treatment of cartilage lesions. 9 , 10 , 22 , 23 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…To emphasize the involvement of filtration in the concentration process, the expression filtered Bone Marrow Aspirate (fBMA) has been introduced. 7 Bone Marrow Aspirate Concentrate in the combination with biomaterials is becoming an increasingly studied and practiced approach in the orthopaedic surgery for the treatment of chondral and osteochondral lesions, which can greatly affect the patients' functioning and quality of life. [8][9][10] The rationale for BMAC augmentation is to leverage the established positive mechanisms of action of MSCs in cartilage regeneration by introducing additional MSCs at the lesion site.…”
Section: Introductionmentioning
confidence: 99%